2013
DOI: 10.1186/1471-2490-13-14
|View full text |Cite
|
Sign up to set email alerts
|

Renal papillary calcification and the development of calcium oxalate monohydrate papillary renal calculi: a case series study

Abstract: BackgroundThe objective of this study is to determine in a case series (four patients) how calcified deposits in renal papillae are associated with the development of calcium oxalate monohydrate (COM) papillary calculi.MethodsFrom the recently collected papillary calculi, we evaluated retrospectively patients, subjected to retrograde ureteroscopy, with COM papillary lithiasis.ResultsThe COM papillary calculi were found to result from subepithelial injury. Many of these lesions underwent calcification by hydrox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…It must be taken into consideration that renal papillary calcification is associated with the development of renal calculi [ 5 , 6 ]. Therefore, close follow-up is necessary for the donor kidney with renal papillary calcification.…”
Section: Discussionmentioning
confidence: 99%
“…It must be taken into consideration that renal papillary calcification is associated with the development of renal calculi [ 5 , 6 ]. Therefore, close follow-up is necessary for the donor kidney with renal papillary calcification.…”
Section: Discussionmentioning
confidence: 99%
“…This deposition, which is similar to extracellular matrix mineralization, can be favoured by oxidative stress and consequent microvascular injury (32). This complex process leads to formation of Randall's plaques, made of apatite, from which calcium-containing stones originate through different attachment mechanisms (33).…”
Section: Physicochemical Basismentioning
confidence: 99%
“…, calcium and phosphate) supersaturation; urinary pH; and a disruption, reduction, or abnormalities in crystallization inhibitors [ 99 ]. Interestingly, in a recent retrospective study, one specific type of papillary stone (calcium oxalate monohydrate, COM) was found to have developed from crystals or organic matter that was attached to the renal papilla [ 101 ]. Indeed, it is believed that renal subepithelial papillary hydroxyapatite calcification is involved in COM stone formation [ 102 ], with recent evidence showing that hydroxyapatite crystals in the papillary, which can form into Randall’s Plaque, can certainly become the nidus of a COM papillary stone [ 103 ].…”
Section: Vascular Calcification and Stone Formation Similarities Tmentioning
confidence: 99%